An ethnography of collaboration :|reflecting on the assemblages of projects for gender mainstreaming in Turkey - İmer, Öznur İlke. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis examines the establishment and implementation of gender mainstreaming (GM) projects enabled by the collaboration between the civil society, public and private sector in Turkey and the new dynamics they create. This study, which aims to observe how gender equality is (re)framed in different contexts and how collaboration is practiced, is based on participant observation carried out in GM activities, and in-depth interviews conducted with actors who play an active role in the establishment of this terrain. First, the thesis introduces a normative framework that includes the new development paradigm, the new configuration of capitalism, and project feminism, with a focus on Turkey’s interaction with this framework. In other words, while illuminating the complex, intertwined processes that contribute to the formation of gender mainstreaming, it proposes to analyze this terrain through this framework and emphasizes the specificity of the Turkish case. Then, it discusses the conflicts that have occurred in the contact zones where different actors with different agendas come together as well as the historical background of these conflicts, how they have been resolved, and the new dynamics that have emerged. Finally, the thesis examines the design phase of the projects, the construction of the trainings, and the roles of the trainers while revealing the informal processes that are not included in the public documents but ensure the formation and continuation of the projects. In sum, this thesis follows the movement of gender within the boundaries drawn by a paradigm that has become dominant today and the questions it produces.
Keywords: Gender mainstreaming -- Turkey.; Civil society -- Turkey.